Adaptive Impact Factor Research Concerning Effectiveness of the Introduction and use of Digital Twins for Oil and Gas Deposits - Afanasyev, V.Ya.; Ukolov, V.F.; Bolshakova, O.I.; Baykova, O.V.; Kislenko, N.A.; Alekseev, A.O. (International Journal of Criminology and Sociology, 2022)
In recent years, there have been significant changes in the conditions of oil production leading to an increase in its cost and wasteful use of resources. This necessitates the search for a system of adaptive factors that can adapt to environmental changes, affect the cost reduction and increase in the efficiency of oil and gas fields. Studies show that this problem needs to be solved on the basis of the creation of digital oil or gas fields being digital counterparts of existing enterprises, which allow preserving nature and use resources economically due to the existing field development at a new qualitative level. However, the transformation of existing fields through their transformation into digital oil or gas fields requires serious justification, and above all, from a financial and economic points of view. At the same time, one should in no case ignore the natural factor contributing to saving, restoring the used oil and gas resources and preserving the external space being the human environment. The purpose of this study is to develop recommendations for assessing the economic efficiency of the implementation of the project concerning a digital oil or gas field being a digital twin of oil or gas enterprise, and their use in practice. Such an assessment will be carried out based on the analysis of the ratio between capital investments and operating costs necessary to create a digital oil or gas field, as well as by comparing the expected costs and benefits derived from its use.